Things We Didn't Talk About When I Was A Girl : A Memoir - Vanasco, Jeannie (Portland, Oregon : Tin House Books, 2019)
In this genre-bending investigation into the trauma of sexual violence, Vanasco interviews her high school rapist, exploring how the assault has impacted his life as well as her own.
Keywords: Vanasco, Jeannie; Rape victims -- Biography -- United States; Rapists -- Interviews. -- United States; Rape -- Biography -- United States; Sex crimes -- Biography -- United States; Women authors, American -- Biography -- 21st century; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY / Women; BIOGRAPHY & AUTOBIOGRAPHY / Survival; Autobiographies; True crime stories